GLP-1RA may have varying effects on cardiac structure in patients with ASCVD depending on BMI - Xu, Ling; Zhu, Dan (Frontiers in Endocrinology, 2024)
Background: GLP-1RA is commonly used in patients with cardiovascular disease due to its significant improvement in the prognosis of atherosclerotic cardiovascular disease (ASCVD). However, previous studies have primarily focused on obese patients, leaving uncertainty regarding whether GLP-1RA can yield similar cardiovascular benefits in individuals with normal or low body weight. Methods: In this study, we enrolled patients with ASCVD to establish a retrospective cohort. Patients receiving GLP-1RA treatment were assigned to the GLP-1RA group, while a control group was formed by matching age and body mass index (BMI) among patients not receiving GLP-1RA treatment. Each group was further divided into subgroups based on baseline BMI levels: normal weight, overweight, and obesity. A six-month follow-up was conducted to assess changes in patient weight, metabolic indicators, and cardiac structure and function. Results: Among the normal weight subgroup, no significant weight change was observed after six months of GLP-1RA treatment (57.4±4.8 vs. 58.7±9.2, p = 0.063). However, significant weight reduction was observed in the other two subgroups (Overweight group: 70.0±9.1 vs. 73.1±8.2, p = 0.003, Obesity group: 90.5±14.3 vs. 95.5±16.6, p<0.001). Regardless of baseline BMI levels, GLP-1RA demonstrated significant glucose-lowering effects in terms of metabolic indicators. However, GLP-1RA have a more significant effect on improving blood lipids in overweight and obese patients. The effects of GLP-1RA on cardiac structure exhibited variations among patients with different baseline BMI levels. Specifically, the improvement in atrial structure was more prominent in patients with normal body weight(LAD: 33.0 (30.3, 35.5) vs. 35.0 (32.5, 37.1), p = 0.018, LAA (18.0 (16.0, 21.5) vs. 18.5 (16.5, 20.5), p = 0.008), while the enhancement in ventricular structure was more significant in obese subjects(LEVDD: 49.8±5.8 vs. 50.2±5.0, p < 0.001, LVMI: 65.1 (56.2, 71.4) vs. 65.8 (58.9, 80.4), p < 0.039). Conclusion: According to the study, the administration of GLP-1RA can have different effects on cardiac structure in patients with different baseline BMI, In obese patients, improvements in ventricular remodeling may be more associated with weight loss mechanisms, while in patients with normal or low BMI, GLP-1RA may directly improve atrial remodeling through GLP-1 receptors in atrial tissue.